2000
DOI: 10.1093/ndt/15.3.324
|View full text |Cite
|
Sign up to set email alerts
|

BK-virus nephropathy in renal transplants—tubular necrosis, MHC-class II expression and rejection in a puzzling game

Abstract: We review BK-virus nephropathy (BKN) as a new complication that increasingly affects renal allografts and causes dysfunction. Since starting in 1996, we have seen 11 cases. Currently, the prevalence of BKN is 3% in our graft biopsies. The diagnosis can only be made histologically. The virus affects tubular epithelial cells that show characteristic intranuclear inclusion bodies. The major reason for impaired graft function and a possible way for viral particles to gain access to the blood via peritubular capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
314
4
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(332 citation statements)
references
References 18 publications
11
314
4
3
Order By: Relevance
“…Several risk factors have been implicated, although there is no consensus. Nickeleit et al found treatment of cellular rejection was more common in patients with BK nephropathy than in controls (137). Other studies have implicated high-dose immunosuppression (particularly tacrolimus and MMF), high-dose steroids, severe ischemia-reperfusion injury, exposure to antilymphocyte therapy, increased number of HLA mismatches between donor and recipient, cadaveric renal transplants, and presence and degree of viremia in the pathogenesis of disease.…”
Section: Bk Polyomavirusmentioning
confidence: 99%
“…Several risk factors have been implicated, although there is no consensus. Nickeleit et al found treatment of cellular rejection was more common in patients with BK nephropathy than in controls (137). Other studies have implicated high-dose immunosuppression (particularly tacrolimus and MMF), high-dose steroids, severe ischemia-reperfusion injury, exposure to antilymphocyte therapy, increased number of HLA mismatches between donor and recipient, cadaveric renal transplants, and presence and degree of viremia in the pathogenesis of disease.…”
Section: Bk Polyomavirusmentioning
confidence: 99%
“…1,3,[7][8][9][10][11][12] Polyomavirus BK (BKV) is a double-stranded non-enveloped DNA virus first isolated from a urine sample obtained from a renal transplant recipient. [13][14][15] Primary infection occurs in childhood and remains in a latent phase most commonly in the kidney. [16][17][18][19] The reactivation of the latent virus is observed in patients with immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinicians accept it as a part of viral-induced parenchymal injury, and reduce immunosuppression after a diagnosis of PVAN. However, others contend that tubulitis is a manifestation of concurrent acute cellular rejection, and advocate increased immunosuppression (6). In an attempt to clarify this controversy, we performed a study to determine the effect of changes in immunosuppression on: (a) histologic viral load, (b) grade of tubulitis, and (c) serum creatinine as a marker of graft function.…”
Section: Introductionmentioning
confidence: 99%